Mass communication - Bittner, John R. (Massachusetts: A Simon y Schuster Company, 1996)
Contents: instructor's section: chapter 1. mass communication: the process. chapter 2. critical - cultural perspective. 3. global perspective. 4. newspapers and newsgathering. 5.
Instructor's section p. 1S-1 - 1S-52
Keywords: Comunicación Social